Equation 4293

Solve the equation and perform the test:

2 (4x + 3) - 2 = 6 - 5 (1 - x)

Correct answer:

x =  -1

Step-by-step explanation:

2(4x+3)2=65(1x)  2 (4 x+3)2=65 (1x)  3x=3  x=33=1  x=1

Did you find an error or inaccuracy? Feel free to write us. Thank you!

Tips for related online calculators
Do you have a linear equation or system of equations and are looking for its solution? Or do you have a quadratic equation?

You need to know the following knowledge to solve this word math problem:

Related math problems and questions: